Evaluación de metales pesados en el fruto del tomate riñón (Solanum lycopersicum) y su influencia en la salsa de tomate artesanal - Santana Vélez, Daniela Patricia (2021)
This study aimed to evaluate the presence of heavy lead metals (Pb) and cadmium (Cd) in the fruit of the kidney tomato (Solanum lycopersicum) harvested in Carrizal Valley, Bolivar canton and its influence on artisanal tomato sauce, being non-experimental research. A sampling was carried out in four crops in three cantons of Manabí province: (Bolívar, Junín and Tosagua) being in the harvest, the collection of samples for analysis using the Method of the Zig-zag scheme, obtaining 50 fruits from each batch giving a total of 1kg per sample. Atomic absorption spectrophotometry was used to determine the concentration of Pb and Cd using the AOAC 20TH 999.11 method. The results found that the fruits showed Levels of Pb between <0.1 to <0.08 and Cd from <0.02 to <0.05, being within the limit allowed in European Commission Regulation (EC) No. 333/2007. In the sauce was determined the transfer in two crops: La Madera y Las Brisas de La Estancilla, Tosagua Canton being <0.1 Pb and <0.02 Cd respectively, indicating that they are within the INEN 1026 and NTON:03 063-06 for and NOM Standards, 130-SSA1 for Cd, as regards the crops in Bolivar and Junín Cantons, these were not analyzed because the levels of Pb and Cd of the fruit are similar to the first analyses, therefore the conditions of the cultivation and process of the sauce do not influence the concentration of heavy metals.